Formation of droplet interface bilayers in a Teflon tube. - Walsh, E; Feuerborn, A; Cook, P (Nature Publishing Group, 2016)
Droplet-interface bilayers (DIBs) have applications in disciplines ranging from biology to computing. We present a method for forming them manually using a Teflon tube attached to a syringe pump; this method is simple enough it should be accessible to those without expertise in microfluidics. It exploits the properties of interfaces between three immiscible liquids, and uses fluid flow through the tube to pack together drops coated with lipid monolayers to create bilayers at points of contact. It is used to create functional nanopores in DIBs composed of phosphocholine using the protein α-hemolysin (αHL), to demonstrate osmotically-driven mass transfer of fluid across surfactant-based DIBs, and to create arrays of DIBs. The approach is scalable, and thousands of DIBs can be prepared using a robot in one hour; therefore, it is feasible to use it for high throughput applications.